Propuesta interiorista de un laboratorio gastronómico y spa en Guayllabamba - Recalde López, Camila Nicole (2020)
The presented degree work is based on the interior design proposal of a Gastronomic lab and spa in one of the Quinta Villa Juliana buildings located in the parish of Guayllabamba, in the panamerican 283, path to the Quinche, the project has 1121.88 m2 and is made for people between 15 and 60 years of age. The objective of this project is to create a Gastronomic laboratory that through its interior design gives spaces that generate familiarization with the gastronomy of the parish like the culture and harvest of fruits like the jicama, custard apple, and avocado and at the same time to develop a space for a spa where visitors not only taste and get to know the gastronomy of the place, but also are able to stay and enjoy a moment of relaxation. This proposal has a gastronomy experience center, in which its visitors through a short tour get to know more about the crop, harvest and process of these three main fruits, a gastronomic laboratory is also implemented, where it is proposed that the chefs creation space be open to the public, also offering a restaurant area. The project also has a spa, where it implements areas for makeup, meditation, and a room for relaxing, a pool, sauna, and hydromassage, through its distribution and proposal and interior – exterior design, allow users to enjoy the nature and climate that the place offers. This project has for a concept the avocado tree, of which unfold many organic forms which are represented a lot in the distribution, mobilization, and in the use of materials, an adequate chromatic is chosen for the proposition of this project working with the Scandinavian style, which is done of the same manner of the floor design, ceiling, illumination, vegetation, furniture design, and the use of spaced out green spaces.